Effect of Repeated Home Quarantine on Anxiety, Depression, and PTSD Symptoms in a Chinese Population During the COVID-19 Pandemic: A Cross-sectional Study - Tang, Qiao; Wang, Ya; Li, Jing; Luo, Dan; Hao, Xiaoting; Xu, Jiajun (Frontiers in Psychiatry, 2022)
Background: Strict quarantines can prevent the spread of the COVID-19 pandemic, but also increase the risk of mental illness. This study examined whether the people who have experienced repeated home quarantine performance more negative emotions such as anxiety, depression, and post-traumatic stress disorder(PTSD) in a Chinese population. Methods: We collected data from 2514 participants in Pi county, Chengdu City and stratified them into two groups. Group 1 comprised 1214 individuals who were quarantined only once in early 2020, while Group 2 comprised 1300 individuals who were quarantined in early 2020 and again in late 2020. Both groups were from the same community. The GAD-7, PHQ-9, and PCL-C scales were used to assess symptoms of anxiety, depression, and PTSD between the two groups. Results: Analyses showed that total PHQ-9 scores were significantly higher in Group 2 than in Group 1 (p < 0.001) and the quarantine times and age are independent predictors of symptoms of depression (p < 0.001). The two groups did not differ significantly in total GAD-7 or PCL-C scores. Conclusion: Increasing quarantine times was associated with moderate to severe depression symptoms, but not with an increase in symptoms of anxiety or PTSD.